Ambition In Woody Allen's Midnight In Paris Movie (2011) : An Individual Psychological Approach - Putranto, Ardy Septian (2012)
The object of the research is Midnight in Paris movie (2011). The major problem of his study is how ambition of Gil reflected in Midnight in Paris movie (2011) based on Individual Psychological Approach. The study analyze the term of structural elements of the movie based on the individual psychological approach. The research is qualitative study. The researcher uses two data sources: primary data source and secondary data source. The primary data is the Midnight in Paris movie. The secondary data are taken from several references such as articles, website about the movie, commentaries, and other about the author or individual psychological material to support the subject matter. The data collection method is library research by collecting both primary and secondary data. The data analysis method is descriptive qualitative analysis based on Individual Psychological approach. The results of the study show; first the structural elements of the movie is a unity and cannot be separated with each other. Second is based on Individual Psychological analysis, it refers to from the ambition of major character that is Gil Pender to finish his novel and Gil tries to finish it to become a famous writer. Gil shows that his ambition can bring him becomes good writer and successful writer. Ambition is imperative in achieving the dream.